Knowledge Domain and Emerging Trends in Podocyte Injury Research From 1994 to 2021: A Bibliometric and Visualized Analysis - Liu, Tongtong; Yang, Liping; Mao, Huimin; Ma, Fang; Wang, Yuyang; Zhan, Yongli (Frontiers in Pharmacology, 2021)
Background: Podocyte injury has a direct causal relationship with proteinuria and glomerulosclerosis and, on a chronic level, can lead to irreversible disease progression. Podocyte injury plays a critically decisive role in the development of proteinuric kidney disease. In recent years, the research on podocyte injury has developed rapidly all over the world. However, no report has summarized the field of podocyte injury as a whole to date. Using bibliometric analysis, this study aimed to evaluate the current state of worldwide podocyte injury research in the last 30 years and identify important achievements, primary research fields, and emerging trends. Methods: Publications related to podocyte injury were retrieved from Web of Science Core Collection. HistCite, VOSviewer, CiteSpace, and the Bibliometrix Package were used for bibliometric analysis and visualization, including the analysis of the overall distribution of annual outputs, leading countries, active institutions and authors, core journals, co-cited references, and keywords. Total global citation score and total local citation score were used to assess the quality and impact of publications. Results: A total of 2669 publications related to podocyte injury were identified. Publications related to podocyte injury tended to increase continuously. A total of 10328 authors from 2171 institutions in 69 countries published studies related to podocyte injury. China (39.46%) was the most prolific country, and the number of citations of studies in the United States (cited 36896 times) ranked first. Moin A Saleem, John Cijiang He, and Zhihong Liu were the top three contributing authors, and Journal of the American Society of Nephrology and Kidney International were the most popular journals in the field. “Diabetic nephropathy” is the primary focus area of podocyte injury research, and “autophagy,” “microRNA,” and “inflammation” were the top keywords of emerging research hotspots. Conclusion: Our research found that global publications on podocyte injury have increased dramatically. Diabetic nephropathy is the main research field of podocyte injury, whereas autophagy, microRNA, and inflammation are the top topics getting current attention from scholars and which may become the next focus in podocyte injury research.